Quality of life in Italian cities: a temporal comparison between before the crisis and after. Issue 4 (10th April 2017) - Bonatti, Guido; Ivaldi, Enrico; Soliani, Riccardo
Abstract : Purpose: The purpose of this paper is to investigate the changes in well-being in the Italian reality, in particular, through the study of major cities. The study is based on a set of data provided by the Italian Institute of Statistics (ISTAT) with the aim to highlight the Italian urban situation and the comparison between the well-being situation assessed in a pre-crisis context and the one observed after it, in order to understand how events have influenced levels of well-being in the main Italian cities. Design/methodology/approach: The paper aims to examine the quality of life (QoL) levels in the metropolitan cities, using data from the URBES report (a report that provides data and information concerning the Italian urban situation), published in 2013, which investigates QoL and well-being in major Italian cities. It is based on the framework of the "Benessere Equo e Sostenibile" report that appraises well-being in Italian regions by a great deal of variables belonging to 12 different dimensions. Using this data source, the authors will proceed to the construction of a composite well-being index. Findings: The paper intends to show how the well-being level in Italian cities has changed in recent years, taking into consideration ten different dimensions of well-being. The need to consider different dimensions of well-being for its comprehensive evaluation is widely discussed in the literature, and the framework provided by ISTAT is innovative in this sense. Originality/value: The paper presents an aggregate measure of well-being in Italian cities on the basis of new theoretical concepts and complete and detailed data.